UNCITRAL Model Law on International Commercial Arbitration and the Reform of the Arbitration Evidence Process in Indonesia - Abimanyu, Enditianto; Sinaga, David Parlinggoman (Universitas Airlangga, 2025)
Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution regulates the arbitration process in Indonesia, but it does not yet provide an adequate system regarding the evidentiary mechanism. One of its main weaknesses is the absence of authority for either arbitrators or courts to compel third parties to present evidence or give testimony, which may result in arbitral awards that are incomplete and/or do not reflect justice. Therefore, a mechanism is needed to assist in the collection of evidence during the arbitration process. Based on this legal issue, this research aims to offer a normative solution to this weakness. The research method used in this study is legal research, with the approaches employed being the Statute Approach and the Conceptual Approach. The conclusion drawn from this study is that one of the applicable solutions to address the weaknesses in the evidence collection system in arbitration is to adopt Article 27 of the UNCITRAL Model Law on International Commercial Arbitration into the national legal system. This provision allows courts to assist in the collection of evidence within certain limits without interfering with the independence of arbitration. Thus, this adoption is expected to strengthen the legitimacy and effectiveness of arbitration in Indonesia, as well as increase business actors’ confidence in this forum as a fair and efficient alternative dispute resolution mechanism.